Whole Genome Sequence-Based Analysis of Bovine Gammaherpesvirus 4 Isolated from Bovine Abortions - Romeo, Florencia; Spetter, Maximiliano Joaquín; Pereyra, Susana Beatriz; Morán, Pedro Edgardo; González Altamiranda, Erika; Louge Uriarte, Enrique Leopoldo; Odeon, Anselmo Carlos; Pérez, Sandra Elizabeth; Verna, Andrea Elizabeth (Multidisciplinary Digital Publishing Institute, MDPI, 2024)
Bovine gammaherpesvirus 4 (BoGHV4) is a member of the Gammaherspivirinae subfamily, Rhadinovirus genus. Its natural host is the bovine, and it is prevalent among the global cattle population. Although the complete genome of BoGHV4 has been successfully sequenced, the functions of most of its genes remain unknown. Currently, only six strains of BoGHV4, all belonging to Genotype 1, have been sequenced. This is the first report of the nearly complete genome of Argentinean BoGHV4 strains isolated from clinical cases of abortion, representing the first BoGHV4 Genotype 2 and 3 genomes described in the literature. Both Argentinean isolates presented the highest nt p-distance values, indicating a greater level of divergence. Overall, the considerable diversity observed in the complete genomes and open reading frames underscores the distinctiveness of both Argentinean isolates compared to the existing BoGHV4 genomes. These findings support previous studies that categorized the Argentinean BoGHV4 strains 07-435 and 10-154 as Genotypes 3 and 2, respectively. The inclusion of these sequences represents a significant expansion to the currently limited pool of BoGHV4 genomes while providing an important basis to increase the knowledge of local isolates.